Ethanol enhances the formation of endogenously and exogenously derived adducts in rat hepatic DNA - Navasumrit, Panida; Ward, T. H; O’Connor, P. J; Nair, Jagadeesan; Frank, Norbert; Bartsch, Helmut (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2001)
To investigate the role of ethanol in chemically-induced carcinogenesis, we exposed Wistar rats to ethanol, either as an acute dose or for prolonged periods in a liquid diet and looked for effects on endogenously and exogenously derived DNA adducts. Changes in the cytochrome P450 protein (CYP 2E1) and its catalytic demethylase activity were also followed in order to provide a sequence of relatively well understood changes that are associated with free radical production and, therefore, potentially capable of affecting DNA. The exocyclic DNA adducts, ethenodeoxyadenosine (εdA) and ethenodeoxycytidine (εdC), known to arise from oxidative stress and lipid peroxidation (LPO) sources, were detected in the liver DNA of Wistar rats at background concentrations of 4-6 (εdA) and 25-35 (εdC) adducts per 109 parent bases. When rats were given either an acute dose of ethanol (5g/kg, i.g.) or exposed for 1 week to ethanol in a liquid diet (5%, w/v), etheno adduct levels were increased ∼2-fold and this was statistically significant for εdC (P<0.05 and P<0.02, respectively) for the two separate treatments. In N-nitrosodimethylamine (NDMA)-treated rats, acute ethanol treatment significantly increased the level of O6-methylguanine (O6-MeG) in hepatic DNA and this was paralleled by a decrease in O6-alkylguanine DNA alkyltransferase (ATase) activity; immunohistochemistry confirmed this increase of O6-MeG in both hepatic and renal nuclei. When rats were given ethanol in the diet and treated with NDMA, O6-MeG levels in hepatic DNA increased at 1 week which coincided with the peak of CYP 2E1-dependent NDMA-demethylase activity. Single cell gel electrophoresis of liver cells showed that after 1 week of exposure to ethanol, there was a small but significant increase in the frequency of DNA strand breaks induced by NDMA (P<0.05); after 4 weeks the increase was 1.4-fold (P<0.01). Our results indicate that exposures to ethanol, which resulted in blood ethanol concentrations similar to those seen in chronic alcoholics and increased levels of expression of the CYP 2E1 protein can exacerbate the DNA damaging effects of endogenous and exogenous alkylating agents. These observations provide indications of possible mechanisms for the carcinogenic or co-carcinogenic action of ethanol.